Effects of different hinge positions on tibial rotation in uniplanar medial opening wedge high tibial osteotomy with three-dimensional tibial models - Jing, Lizhong; Ren, Yulian; Wang, Shaoshan; Yang, Jiushan; Wang, Jian (Frontiers in Surgery, 2024)
BackgroundTo investigate the effects of different hinge positions in the sagittal and axial planes on distal tibial rotation (DTR) during medial opening wedge high tibial osteotomy (MOWHTO) with three-dimensional tibial models.MethodsPreoperative CT data from 30 knee joints in 30 patients who underwent surgery for varus malalignment of knee were included. 1 standard hinge position (0°), 6 axial planes (±5°, ±10°, ±15°), and 6 sagittal planes (±5°, ±10°, ±15°) hinge positions were defined and virtual uniplanar osteotomy was performed. The correction angle of each model was generated using Fujisawa's point. Participants’ baseline characteristics, radiologic parameters and DTR were measured. One-Way Repeated Measures ANOVA and single factor linear regression analysis were used to analyze the association between tibial rotation and hinge position in the sagittal and axial planes.ResultsWe found a clear linear correlation between changes in hinge position in the sagittal plane and DTR. The changes in DTR were the smallest when the hinge position was at 5°, where internal or external rotation of the DTR may occur. When the front aspect of hinge axis rotated distally, DTR tended towards internal. Meanwhile, when the front aspect of hinge axis rotated proximally, DTR tended towards external. There were no correlations with every hinge axis position in the axial plane.ConclusionsIt is sagittal but not axial hinge axis affects DTR in uniplanar MOWHTO with three-dimensional tibial models. In the sagittal plane, every change in hinge position was significantly linearly correlated with DTR. However, no linear correlations were observed between every hinge position change in the axial plane.